Change Management in the Digital Era: Determinants of Successful Technology Adoption in Large Organizations - Imam Jayanto; Murthada; Stievanno Eucharisto A. Mondigir; Patricia Rachel Tesalonika Woyongan (Journal Management & Economics Review (JUMPER), 2026)
The rapid acceleration of digital transformation has compelled large organizations to adopt new technologies to enhance operational efficiency, competitiveness, and strategic agility. However, successful technology adoption remains a complex organizational challenge influenced by multiple structural and human factors. This study investigates the determinants of successful technology adoption in large organizations, focusing on five key variables: change readiness, leadership support, digital competency, organizational culture, and training effectiveness. Using a quantitative research design and structural equation modeling (SEM), data were collected from employees across large organizations undergoing digital transformation initiatives. The results reveal that change readiness has the strongest positive effect on technology adoption, followed by leadership support, digital competency, and training effectiveness. Organizational culture, while statistically significant, exhibits a comparatively weaker influence. These findings highlight that technology adoption is not merely a technical process but a multifaceted organizational change effort requiring psychological preparedness, competent leadership, continuous skill development, and a supportive culture. The study contributes to the growing body of digital transformation literature by offering an integrated model of adoption determinants and provides practical insights for leaders seeking to optimize technology implementation strategies. Overall, the research underscores the need for holistic change management approaches to ensure sustainable and effective technology adoption in the digital era.